Challenges And Development Of The ILMAN Innovative For Arabic Language Leaning As A Foreign Language For Individuals With Visual Impairments - Ijlal Saja; Azman Che Mat; Nurshaza Farah Md Sharif; Zamzuri Ghani; Sumitha Thavanendran; Akmaluddin Akmaluddin; Nor Afifa Nordin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Mastering a foreign language fosters self-reliance, enhances employability, and creates opportunities for participation in local and global contexts. For individuals with visual impairments, language acquisition is particularly significant as it grants access to knowledge, facilitates social interaction, and supports career advancement. The objectives of this study are to identify the challenges and develop an innovative approach to Arabic language learning (ILMAN) for visually impaired learners, with emphasis on innovation (I), inclusive learning (L), multimedia (M) support, flexible accessibility (A-anywhere), and continuous engagement (N-nonstop). These dimensions are combined to establish a sustainable framework that addresses learners’ needs. Assistive technologies such as electronic Braille displays, screen readers, and audio resources are crucial in overcoming barriers. The research adopted a qualitative design and was conducted in Kuala Lumpur and Ipoh, Malaysia. Eight participants with visual impairments were selected using purposive and snowball sampling to ensure representation of diverse experiences. Data were collected through interviews and analyzed thematically to identify challenges and effective strategies. The theme results show that access to learning materials (20.6%) is the most critical issue, reflecting a shortage of Braille resources. Religious-based methods such as memorization and talaqqi remain dominant (27.3%), indicating that Arabic Language Learning (ALL) for blind students is still largely centered on religious practice. At the same time, Braille displays and teacher support (40%) highlight the importance of assistive technology and motivation, with the ILMAN innovation concept offering an inclusive and flexible solution. This is expected to assist visually impaired learners in developing spoken Arabic communication skills. Future studies are encouraged to expand these practices and assess their application across other languages and contexts.